Kiprah Syaikh Maulana Malik Ibrahim pada Islamisasi Gresik Abad ke-14 M dalam Babad Gresik I - Syarifah Wardah el Firdausy; Nur Azizah; Solichah Solichah; Umi Habibah; Dwi Retty Warsadila; Dwi Istiqomah; Ulil Ulifia Husnawati; Sita Arum Damayanti (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2020)
This study aims to describe the process of Islamization of Gresik in the 14th century brought by Shaykh Maulana Malik Ibrahim and recorded in the Babad Gresik I. This study uses the qualitative research method based on the study of literature of Babad Gresik I manuscript which has been in the form of Indonesian translation book written by Soekarman (1990). The results of this study are (1) The profile of Shaykh Maulana Malik Ibrahim, including: (a) The arrival of Shaykh Maulana Malik Ibrahim in Gresik region recorded in Babad Gresik I and (b) The death of Shaykh Maulana Malik Ibrahim recorded in Babad Gresik I as well as (2) The methods of da'wah conducted by Shaykh Maulana Malik Ibrahim in the process of Islamization of Gresik in the 14th century including two methods, namely: (a) Da'wah methods through the trade/commerce routes recorded in Babad Gresik I and (2) Da'wah methods through education Islamic boarding schools recorded in Babad Gresik I. Overall, it can be seen that there were some contributions of Syaykh Maulana Malik Ibrahim in the process of Islamization in the 14th century in Gresik that was recorded in Babad Gresik I.